Preparation and characterization of activated carbons from tobacco stem by chemical activation - Chen, R.; Li, L.; Liu, Z.; Lu, M.; Wang, C.; Li, H.; Ma, W.; Wang, Shaobin (2017)
© 2017 A&WMAActivated carbons were prepared from tobacco stem by chemical activation using potassium hydroxide (KOH), potassium carbonate (K2CO3), and zinc chloride (ZnCl2). The effects of the impregnation ratio (activating agent/precursor) and activating agents on the physical and chemical properties of activated carbons were investigated. The textual structure and surface properties of activated carbons were characterized by nitrogen (N2) adsorption isotherm, scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), x-ray photoelectron spectroscopy (XPS), and thermogravimetry (TG). ZnCl2, acting as a superior activating agent compared to the others, produced much more porosity. The maximum specific surface area reached 1347 m2/g, obtained by ZnCl2 activation with an impregnation ratio of 4.0. Moreover, ZnCl2 activation yielded products with an excellent thermostability, attributed to different activation mechanisms. Various oxygen functions were detected on the activated carbon surface, and hydroxyl and ester groups were found to be in the majority. Implciations: Tobacco stem, the residue from cigarette manufacturing, is usually discarded as waste, leading to serious resource waste and environmental problems. This study provides an effective utilization available for this solid residue by using it as the starting material in the preparation of activated carbon with chemical activation. Activated carbons with high specific area and various surface functions have been prepared, and the effects of the amount and type of activating agents on the physical and chemical properties of activated carbon were investigated as well.